Aplikasi Tuning Metode Cohen-Coon pada Pengendali pH di Tangki Neutralisasi, Unit Pengolahan Limbah - Profiyanti Hermien Suharti; Khalimatus Sa'diyah (Eksergi, 2019)
Wastewater generated in industry should be treated, in order to meet the standards set by the Government. pH became important parameters in the process of wastewater treatment. One of waste in industrial synthetic fibers contain ions that make pH of wastewater ranged from 2 to 3. The value of the threshold for the pH of the wastewater, based on regulation of the Minister of environment, ranged from 6 to 9. The main process to achieve this standar was the neutralization process. In order to fulfilment the pH target, pH controller has been used to monitor the pH at neutralization tank. pH controller which is used is a type of PID (proportional, integral, derivative) controller. The PID parameter that used in the controller are proportional gain (Kc) 10, integral time (τi) 1 minutes and 10 second as derivative time (τD). This parameter yields an oscillation response. This research aims to get the optimum PID parameters that can be applied to keep wastewater pH around 7. The experiment results show that the parameters of the PID controller Kc = 0.251, τi = 151 second = 2.51 minutes and τD = 12.5 second, had better performance than the PID controller parameters used previously.